PENGARUH RIWAYAT ATOPIK TERHADAP DERMATITIS TANGAN PADA PERAWAT RSUD DR. MOEWARDI - Anggraini, Efa (2017)
ABSTRACT Effect of Atopik History on Hand Dermatitis among Nurses in DR. Moewardi Surakarta Hospital Efa Anggraini, Ratih Pramuningtyas Medical School, Muhammadiyah Surakarta University Background: In 2016, DR. Moewardi Hospital begins Accreditation of JCI, so that there are many improvement programs at the hospital, one of them was Handwashing Program for healthcare provider. Besides contacts with water, handwash also using irritant materials and endogenous factors such as history of atopik can cause hand dermatitis. Goals: This study aim to know the effect of atopik history on hand dermatitis in DR. Moewardi Surakarta Hospital. Method: This was an observational analytic study with cross sectional approach that conducted among nurses in DR. Moewardi Surakarta Hospital. We used primary data from a standard questionnaire, Nordic NOSQ-UK-SHORT-2002, which has been translated Into Indonesian. The sampling technique was purposive sampling. Subject of this study was all nurses in DR. Moewardi Surakarta Hospital. Data were collected and analyzed by SPSS 17.0 program. Result: Statistical test using Spearman test showed significant value 0.01, so it meant there was an influence of atopik history on hand dermatitis statistically. Data from the analysis showed correlation coefficient of 0.42 that meant that person who has history of atopik dermatitis was moderately correlated to the occurrence of hand dermatitis. Conclusion: There is an effect of atopik history on hand dermatitis among nurses in DR. Moewardi Surakarta Hospital. __________________________________________________________________ Key words: Atopik history, Hand dermatitis